Dual RNA-Seq characterization of host and pathogen gene expression in liver cells infected with Crimean-Congo Hemorrhagic Fever Virus. - Robert A Kozak; Russell S Fraser; Mia J Biondi; Anna Majer; Sarah J Medina; Bryan D Griffin; Darwyn Kobasa; Patrick J Stapleton; Chantel Urfano; Giorgi Babuadze; Kym Antonation; Lisa Fernando; et al. (Public Library of Science (PLoS), 2020)
Crimean-Congo hemorrhagic fever virus (CCHFV) is a tick-borne virus that can cause a hemorrhagic fever in humans, with a case fatality rate of up to 40%. Cases of CCHFV have been reported in Africa, Asia, and southern Europe; and recently, due to the expanding range of its vector, autochthonous cases have been reported in Spain. Although it was discovered over 70 years ago, our understanding of the pathogenesis of this virus remains limited. We used RNA-Seq in two human liver cell lines (HepG2 and Huh7) infected with CCHFV (strain IbAr10200), to examine kinetic changes in host expression and viral replication simultaneously at 1 and 3 days post infection. Through this, numerous host pathways were identified that were modulated by the virus including: antiviral response and endothelial cell leakage. Notably, the genes encoding DDX60, a cytosolic component of the RIG-I signalling pathway and OAS2 were both shown to be dysregulated. Interestingly, PTPRR was induced in Huh7 cells but not HepG2 cells. This has been associated with the TLR9 signalling cascade, and polymorphisms in TLR9 have been associated with poor outcomes in patients. Additionally, we performed whole-genome sequencing on CCHFV to assess viral diversity over time, and its relationship to the host response. As a result, we have demonstrated that through next-generation mRNA deep-sequencing it is possible to not only examine mRNA gene expression, but also to examine viral quasispecies and typing of the infecting strain. This demonstrates a proof-of-principle that CCHFV specimens can be analyzed to identify both the virus and host biomarkers that may have implications for prognosis.